Pro-regime militias and civil war duration - Aliyev, Huseyn (Terrorism and political violence, 2020)
Research on civil war duration has tended to focus almost exclusively on governments and rebels as actors accounting for the longevity of armed conflicts. The impact of extra-dyad actors has thus far been absent from the analysis of factors contributing to civil war duration. This study contributes to both research on civil war duration and multi-actor models of intrastate conflicts by extending the analysis beyond the government-rebel dichotomy. With the focus on pro-regime militias, this article investigates whether the deployment of extra-dyad actors increases the duration of civil wars. Survival analysis models conducted on the sample of 250 civil war episodes between 1991 and 2015 reveal that participation of pro-regime militias in intrastate warfare has consistent association with the incidence of longer civil wars.